2022
DOI: 10.1177/08862605221132785
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Obesogenic Behaviors Associated With Bullying Roles Among 100,794 Adolescents

Abstract: Obesogenic behaviors have been individually associated with bullying during adolescence. However, physical activity, sedentary behavior, and diet manifest themselves in synergy and even behavioral profiles in which positive and negative behaviors coexist can be more positively associated with psychosocial outcomes. The present study aimed to analyze the association between clusters of obesogenic behaviors and different bullying roles in Brazilian adolescents. This cross-sectional study used data from the Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Crude and adjusted binary logistic regression models were applied to evaluate the associations between exposure (the clusters) and social isolation variables (perceived loneliness and having close friends). For each model, a set of covariates was selected based on empirical and theoretical evidence [12] (see tables notes); The Rao Scott chi-square test were performed to evaluate the association of each covariate and both outcomes of social isolation. Significant predictors at p-value < 0.2 were retained and included in the adjusted models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crude and adjusted binary logistic regression models were applied to evaluate the associations between exposure (the clusters) and social isolation variables (perceived loneliness and having close friends). For each model, a set of covariates was selected based on empirical and theoretical evidence [12] (see tables notes); The Rao Scott chi-square test were performed to evaluate the association of each covariate and both outcomes of social isolation. Significant predictors at p-value < 0.2 were retained and included in the adjusted models.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Matias and colleagues reported that adolescents in healthier clusters were more likely to be satisfied with their body image [2]. More recently, a large survey of Brazilian adolescents found that obesogenic clusters with more positive behaviors than negative ones were associated with prosocial attitudes and reduced adolescent bullying [12].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation